2009
DOI: 10.1074/jbc.m109.029876
|View full text |Cite
|
Sign up to set email alerts
|

Translocator Protein 2 Is Involved in Cholesterol Redistribution during Erythropoiesis

Abstract: Translocator protein (TSPO) is an 18-kDa cholesterol-and drug-binding protein conserved from bacteria to humans. While surveying for Tspo-like genes, we identified its paralogous gene, Tspo2, encoding an evolutionarily conserved family of proteins that arose by gene duplications before the divergence of avians and mammals. Comparative analysis of Tspo1 and Tspo2 functions suggested that Tspo2 has become subfunctionalized, typical of duplicated genes, characterized by the loss of diagnostic drug ligandbinding b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 47 publications
7
87
0
Order By: Relevance
“…This led to the conclusion that TSPO2 may be involved in heme availability for the assembly of hemoglobin (Nakazawa et al 2009). In contrast, the study with mouse and human TSPO2 was an extrapolation of previous work on TSPO and steroidogenesis from the same authors, and suggested that TSPO2 is involved in cholesterol uptake and trafficking in erythroid cell types (Fan et al 2009). At the present time, there are no gene-knockout models to study loss-of-function resulting from TSPO2 deletion, and understanding of its function remains rudimentary.…”
Section: Is Tspo2 An Isofunctional or Heterofunctional Homolog?mentioning
confidence: 44%
See 3 more Smart Citations
“…This led to the conclusion that TSPO2 may be involved in heme availability for the assembly of hemoglobin (Nakazawa et al 2009). In contrast, the study with mouse and human TSPO2 was an extrapolation of previous work on TSPO and steroidogenesis from the same authors, and suggested that TSPO2 is involved in cholesterol uptake and trafficking in erythroid cell types (Fan et al 2009). At the present time, there are no gene-knockout models to study loss-of-function resulting from TSPO2 deletion, and understanding of its function remains rudimentary.…”
Section: Is Tspo2 An Isofunctional or Heterofunctional Homolog?mentioning
confidence: 44%
“…Unlike TSPO expression that is observed at high levels in cells active in lipid storage/metabolism (Fig. 2), TSPO2 expression appears restricted to the bone marrow (Fan et al 2009, Nakazawa et al 2009), and has not been detected in steroidogenic tissues (confirmed in Morohaku et al 2014, Tu et al 2014. Subcellular localization of TSPO2 using specific antibodies has not been performed; localization based on overexpression studies using C-terminal GFP/DsRed-TSPO2 fusion proteins (chicken, mouse and human) in cell lines have led to conflicting proposals.…”
Section: Is Tspo2 An Isofunctional or Heterofunctional Homolog?mentioning
confidence: 99%
See 2 more Smart Citations
“…1C). When 0.1 µM of NBD-cholesterol was used, which represents a concentration reported in several previous studies (10,19,20), for up to 12 h of incubation, real-time imaging yielded dim fluorescent images. This finding was confirmed by quantitative FI detection, in which the FI of the cell lysate was undetectable following 12 h incubation.…”
Section: Nbd-cholesterol Uptake and Metabolism In Thp-1-derived Macromentioning
confidence: 99%